ALGUNAS EXPRESIONES MEDIDAS EN LA RELIGIOSIDAD POPULAR. - Caro Hernández, Isela (Cuadernos de Literatura del Caribe e Hispanoamérica, 2010)
En el presente artículo se examinan las relaciones entre procesos de mediaciones agenciados por medios masivos de comunicación y las expresiones de la religiosidad popular, con énfasis en el examen de casos en Cartagena de Indias. Para ello, se exponen brevemente consideraciones sobre lo popular y la religiosidad popular, se examina la trama de conceptos que se articula en las nociones de mediaciones, matrices tradicionales de la cultura popular y procesos de constitución de “imaginarios populares internacionales”, aplicándolos a expresiones religiosas populares en Cartagena de Indias. PALABRAS CLAVES Matrices culturales, mediaciones, religiosidad popular, “cultura mundo”. ABSTRACT In the present article the relations are examined between processes of mediations obtained by massive means of communication and the expressions of the popular religiousness, emphatically in the examination of cases in Cartagena de Indias. For it, considerations are exposed brief on the popular thing and the popular religiousness, there is examined the plot of concepts that is articulated in the notions of mediations, traditional counterfoils of the popular culture and processes of constitution of “imaginary popular in ternational”, applying them to religious popular expressions in Cartagena de Indias. KEY WORDS Cultural counterfoils, mediations, popular religiousness, “culture world”.